Precise study of the Z/γ* boson transverse momentum distribution in pp̄ collisions using a novel technique - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; Alves, G. A.; Ancu, L. S.; et al. (American Physical Society (APS), 2011)
Using 7.3fb-1 of pp̄ collisions collected by the D0 detector at the Fermilab Tevatron, we measure the distribution of the variable φη*, which probes the same physical effects as the Z/γ* boson transverse momentum, but is less susceptible to the effects of experimental resolution and efficiency. A QCD prediction is found to describe the general features of the φη* distribution, but is unable to describe its detailed shape or dependence on boson rapidity. A prediction that includes a broadening of transverse momentum for small values of the parton momentum fraction is strongly disfavored. © 2011 American Physical Society.